Development of Electronic Teaching Materials with the SAVI Approach to Enhance Students' Problem-Solving Skills - Rusmawati, Ida; Arifuddin, Muhammad; Suyidno, Suyidno (Jurnal Pendidikan Fisika dan Teknologi (JPFT), 2023)
Students’ problem-solving skills are still considered low. Teachers can motivate students in learning by using interactive teaching materials. This study aims to analyze the feasibility of electronic teaching materials with the SAVI approach to improve students' problem-solving skills in static fluid material. The electronic teaching materials consist of lesson plans, teaching materials, student worksheets, and problem-solving tests. This study was included in research and development using the ADDIE model and tested were carried out on 19 students of class XI MIPA MA Sultan Sulaiman. Data collection used electronic teaching material validation instruments and response questionnaires. The data analysis technique was carried out in a quantitative descriptive. The results showed that: (1) the result of the validation of electronic teaching materials including lesson plans, teaching materials, worksheets, and problem-solving tests were in the valid category, and (2) student responses in terms of understanding the contents of electronic teaching materials, clarity of study instruction and information, suitability of electronic teaching material appearance, motivation, interest, curiosity, asking and responding to questions, and problem- solving have fulfilled the practical category. It is concluded that the electronic teaching materials developed with the SAVI approach are feasible to improve students' problem-solving skills on static fluid material. This teaching material can be an alternative for educators in equipping students with 21st century competencies, especially problem-solving skills.